Portable Python Projects: Run Your Home on a Raspberry Pi - Riley, Mike (Pragmatic Programmers, LLC, 2022)
Get to know the latest Raspberry Pi hardware, and create awesome automation solutions for home or work that don't require an electronics degree, cumbersome add-ons, or expensive third-party subscription services. Create easy-to-run Python scripts on your own that make your Pi do things that would have required a team of automation experts to build only a few years ago. Connect to and control popular home automation lighting systems from a Raspberry Pi. Trigger autonomous actions based on movement, temperature, and timer events. Power on your own computer and appliances using your voice. Remotely control infrared-enabled consumer electronics, create chatbots to retrieve personalized items of interest, and implement a temperature-monitoring room fan. These are just some of the projects that the book will show you how to make. Most projects can be completed and operational in under an hour, and do not require any messy schematics or a spaghetti bowl of wires and breadboard-attached circuits to operate. Control your home or office exactly the way you want instead of relying on an expensive mysterious box of third-party technology to do it for you.